Study on the Safety of Radioactive Waste Management in the Radiology Laboratory of Indonesian Hospital - Ophelia, Nadya; Jandhana, I.B Putra; Jupriyanto; Ruyat, Yayat; Hafizah, Mas Ayu Elita; Simanjuntak, Junita Dewi Sari (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the uses of radioactive sources is in the field of health, where they are used in hospitals for radiotherapy, nuclear medicine, and radiodiagnostics. Nevertheless, the use of nuclear technology in the health sector produces radioactive waste substances that pose health and environmental risks, and have the potential to be misused by irresponsible groups and terrorists to create radiological weapons that are used in crimes and pose a threat to security. Any activity that utilizes radioactive substances must pay attention to radioactive waste management, which applicable regulations must appropriately manage. The research method used is descriptive research with a qualitative approach, and data collection techniques are used with literature review methods. Radioactive waste produces alpha, beta, and gamma radiation. Radioactive waste treatment techniques can be carried out by separation, storage, transportation, treatment, and final disposal. Governments, hospitals, relevant organizations, and communities should work together to improve the safety of radioactive waste management and protect the environment and human health. It is essential to understand the types of radioactive waste substances, comply with applicable rules and regulations, implement appropriate radioactive waste treatment techniques, and raise awareness about the dangers of radioactive waste substances